Louisa May Alcott - Gormley, Beatrice; Nang ChanYeema (New York, USA Aladdin Paperbacks, 1999)
Traces the life of the author of the well-loved stories of the March sisters, Little Women and their sequels.
Keywords: Adult Nonfiction